System Dynamic Approach to Analyzing the Watermelon Supply Chain in Sidoarjo, East Java - Ubaiyi, R. Vanji Abdillah; Donoriyanto, Dwi Sukma; Rahmawati, Nur (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2024)
The supply chain system will greatly affect the distribution channel that will be targeted, thereby affecting the availability of products and also the fulfillment of needs for the community. Sidoarjo Regency has the potential to produce watermelons independently; this is supported because Sidoarjo Regency is included in the Gerbangkartasusila region, with Surabaya City as one of the main supporting districts. Watermelon fruit has a very abundant amount of production in Sidoarjo Regency, but watermelon fruit is a seasonal fruit with erratic public consumption and tends to decrease, causing an excess supply of watermelon. Therefore, this research was conducted to determine supply chain behavior, then model and simulate it, as well as design a model for improving the watermelon supply chain in Sidoarjo Regency. Through a system dynamics simulation approach using Vensim software, the results show that the amount of watermelon stock in Sidoarjo is affected by production, consumption, and depreciation values. Then, the current total production of watermelons will be 1110 quintals in 2021. Through a simulation of the improvement model design with the addition of other regional distributions and the assumption of a distribution of 350 tons/year for the next 5 years, the supply of watermelons is still able to meet the needs of the people of Sidoarjo Regency. The improvement model reduces excess inventory in Sidoarjo Regency.